THU0258 NERVOUS SYSTEM INVOLVEMENT IN PRIMARY SJÖGREN'S SYNDROME. (June 2019) - Andreu, Jose Luis; Sánchez-Piedra, Carlos; Castro, Monica Fernandez; Taboada, Victor Martinez; Olive, Alejandro; Rosas, Jose; Menor-Almagro, Raúl; Lozano, Beatriz Rodriguez; García-Aparicio, Ángel; López-Longo, Francisco J; Arija, Sara Manrique; García Vadillo, Jesús Alberto; et al.
Abstract : Background: Primary Sjögren's syndrome (pSS) is a systemic autoimmune disease characterized by the involvement of the exocrine glands, mainly salivary and lacrimal glands. Approximately half of patients will experience extraglandular complications throughout their evolution. Objectives: To characterize the involvement of the nervous system (NS) in patients with pSS. Methods: Multicenter cross-sectional study of a cohort of patients with pSS, constructed by random selection of pSS patients fulfilling the 2002 American-European Consensus Criteria for pSS 1 from 33 rheumatology units. Through review of clinical records and interview with patients, demographic, clinical, analytical, therapeutic data and disease activity indexes were collected. Univariate analysis was done by Chi square test, Mann-Whitney U test and Student's t test. Multivariate analysis was done by linear logistic regression. A p <0.05 was considered significant. Patients signed an informed consent. The study was authorized by the ethics committees. Results: 437 patients were included (95% women, median age of 58 years). 65 patients developed NS involvement: 26 patients central NS, 31 peripheral NS and 8 both. Multivariate analysis showed association between NS involvement and atherosclerotic stroke (OR 10.4, 95% CI 2.8-38.5), ear disease (OR 2.1, 95% CI 1.1-4.2) and myopathy (OR 6.5, 95% CI 1.3-31, 6). Patients with NS involvement had higher probability of being treated with glucocorticoids (OR 3.3, 95%CI 1.5-7.2) and cyclophosphamide (OR 6.8, 95% CI 1.5-31). Conclusion: 15% of patients with pSS develope NS involvement that is associated with atherosclerotic stroke, ear disease and myopathy. Reference: [1] Vitali C. et al. Ann Rheum Dis 2002; 61:554 Disclosure of Interests: Jose Luis Andreu: None declared, Carlos Sánchez-Piedra: None declared, Monica Fernandez Castro: None declared, Victor Martinez Taboada: None declared, Alejandro Olive: None declared, Jose Rosas Consultant for: Abbvie, Amgen, Bristol, Janssen, Lilly, Merck Sharp & Dohme, Pfizer, UCB Pharma, Speakers bureau: Abbvie, Amgen, Bristol, Janssen, Lilly, Merck Sharp & Dohme, Pfizer, UCB Pharma, Raúl Menor-Almagro: None declared, Beatriz Rodriguez Lozano: None declared, Ángel García-Aparicio: None declared, Francisco J López-Longo: None declared, Sara Manrique Arija Speakers bureau: ABBvie, MSD, Janssen, Lillly, Roche, Pfyzer, Novartis., Jesús ALberto García Vadillo: None declared, Susana Gil: None declared, Ruth López González: None declared, J. Narváez Consultant for: Bristol-Myers Squibb, Carles Galisteo: None declared, Jorge Juan Gonzalez Martin: None declared, M E Ruiz: None declared, Iñigo Rúa-Figueroa: None declared, Oscar Illera: None declared, Lurdes Romani: None declared, Sheila Melchor: None declared, Begoña Moreira: None declared, Enrique Raya: None declared, Jose M Pego-Reigosa: None declared, Natalia Cid Boza: None declared, Enrique Judez: None declared, Clara Moriano: None declared, Vicente Torrente: None declared, Héctor Corominas: None declared, Blanca Garcia-Magallon: None declared, Carlos Guillén-Astete: None declared, Ivan Castellví Consultant for: I received fees less than 5000USD as a consultant for Kern and Actelion, Paid instructor for: I received fees less than 2000USD as a instructor for Boehringer -Ingelheim, Novartis and Gebro, Speakers bureau: ND, Cristina Bohórquez: None declared, Javier Loricera: None declared, Joaquín Belzunegui: None declared